Transgelin Inhibits the Malignant Progression of Esophageal Squamous Cell Carcinomas by Regulating Epithelial–Mesenchymal Transition - Yang, Boli; Chen, Qiuyu; Wan, Changshan; Sun, Siyuan; Zhu, Lanping; Zhao, Zhizhong; Zhong, Weilong; Wang, Bangmao (Frontiers in Oncology, 2021)
Objective: This article investigates the role of Transgelin (TAGLN) in the epithelial–mesenchymal transition (EMT) of esophageal squamous cell carcinomas (ESCC) and its possible mechanism of inhibiting the invasion of these cancers. Methods: Tissue specimens and clinical information of patients with ESCC were collected to analyze the relationship between Transgelin expression level and prognosis of patients with ESCC. Transgelin siRNA was used to knock down Transgelin expression. The expression of Transgelin in Eca-109 and KYSE-150 cells was overexpressed by Transgelin-overexpressing plasmid. The effects of Transgelin overexpression and knockdown on the proliferation of Eca-109 and KYSE-150 cells were examined by Transwell chamber, scratch assay, and CCK-8 cell activity assay. RT-PCR and Western blot were used to detect the effect of Transgelin overexpression or knockdown on the mRNA and protein expressions of E-cadherin and Vimentin. TCGA data were used to analyze Transgelin co-expressed genes and further study the GO and KEGG enrichment analysis results under the influence of Transgelin. Results: The expression of Transgelin was low in ESCC, and its expression level was positively correlated with the prognosis of patients with ESCC. The targeted Transgelin siRNA and Transgelin-overexpressing plasmid can effectively regulate the expression of Transgelin mRNA and protein in Eca-109 and KYSE-150 cells. After overexpression of Transgelin, the invasion and proliferation abilities of Eca-109 and KYSE-150 cells were significantly decreased compared with those of the control group (P < 0.05). However, Transgelin knockdown could promote the proliferation, migration, and invasion of ESCC cells. The overexpression of Transgelin inhibits EMT in ESCC. With the increase of Transgelin expression in Eca-109 and KYSE-150 cells, the expression of E-cadherin increased, while the expression of Vimentin decreased, and the difference was statistically significant (P < 0.05). Conclusion: Transgelin can inhibit the malignant progression of ESCC by inhibiting the occurrence of EMT.